A CGE approach to measuring the impacts of EU structural funds in a small open economy - Fortuna, Mário (2019)
The present work studies the European Union (EU) funds in a regional context, while assessing the impact of EU funds on the gross domestic product (GDP) and employment of the Autonomous Region of the Azores. The theoretical model is based on a modeling platform for the Azorean economy, supported by a dynamic multi-sectoral Computable General Equilibrium model (CGE) - AzorMod, which incorporates the economic behavior of six agents: firms, households, the regional government, the central government, the European Commission and an external sector. Using simulations, we study the impact of eliminating EU funds from the Azorean economy. The study reveals that the absence of EU funds causes a reduction in public consumption and in consumer well-being and an increase in investment. GDP and employment decrease in the first year of the simulations. The GDP level is only recovered at the end of ten years when there are no EU transfers and employment at the end of one year. After this period, the estimated values, without EU funds, exceed the projected values for the scenario that include community funds.